Hubungan Self Efficacy dengan Kepatuhan Diet pada Penderita Hipertensi di Puskesmas Sawah Besar Jakarta Pusat - Anggraeni, Ryana Iga; Nia Rosliany; Yarwin Yari (Poltekkes Kemenkes Kupang, 2025)
Background: Hypertension is a non-communicable disease with a prevalence continues to increase nationally and globally. This condition can cause serious complications such as stroke, kidney failure, and heart disease. Hypertension management is not only through drug therapy, but also includes healthy lifestyle changes and dietary compliance. One factor that supports compliance is self-efficacy, namely an individual's belief in their ability to perform certain behaviors, including following a hypertension diet. Objective: To determine the relationship between self-efficacy and dietary compliance in hypertension patients at the Sawah Besar Community Health Center, Central Jakarta. Method: This study used a quantitative approach with a cross-sectional design. The data analysis technique used in this study was the Spearman rho test with a sample of 190 respondents. Results: The results showed that the majority of respondents had high self-efficacy and were compliant with the diet. Based on the results of statistical tests, the p value = 0.000 and r value 0.922 indicated a very strong relationship between self-efficacy and dietary compliance.